2020
DOI: 10.1128/msphere.00921-19
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plasmodium falciparum Calcium-Dependent Protein Kinase 5 (PfCDPK5) on the Late Schizont Stage Phosphoproteome

Abstract: Protein kinases are important mediators of signal transduction in cellular pathways, and calcium-dependent protein kinases (CDPKs) compose a unique class of calcium-dependent kinases present in plants and apicomplexans, including Plasmodium parasites, the causative agents of malaria. During the asexual stage of infection, the human malaria parasite Plasmodium falciparum grows inside red blood cells, and P. falciparum calcium-dependent protein kinase 5 (PfCDPK5) is required for egress from the host cell. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Due to the low expression of PfApiAT9-GFP -in agreement with the transcript levels of apiat9 in these stages 37,42,43 -no conclusive localization could be delivered. The observed PPM localization of the investigated ApiATs is in concordance with published data, since i) the P. berghei ApiAT8 homologue was shown to be a general cationic amino acid transporter of the PPM 29,30 , ii) PfApiAT8 has recently been localized to the PPM using an overexpression approach 31 , and iii) in T. gondii several ApiATs (TgApiAT1, TgApiAT2, TgApiAT3-1, TgApiAT3-2, TgApiAT3-3, TgApiAT5-3, TgApiAT6-1 and TgApiAT6-3) have been located at the PPM as well 25,29,30,32,33,44 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Due to the low expression of PfApiAT9-GFP -in agreement with the transcript levels of apiat9 in these stages 37,42,43 -no conclusive localization could be delivered. The observed PPM localization of the investigated ApiATs is in concordance with published data, since i) the P. berghei ApiAT8 homologue was shown to be a general cationic amino acid transporter of the PPM 29,30 , ii) PfApiAT8 has recently been localized to the PPM using an overexpression approach 31 , and iii) in T. gondii several ApiATs (TgApiAT1, TgApiAT2, TgApiAT3-1, TgApiAT3-2, TgApiAT3-3, TgApiAT5-3, TgApiAT6-1 and TgApiAT6-3) have been located at the PPM as well 25,29,30,32,33,44 .…”
Section: Discussionsupporting
confidence: 90%
“…P. falciparum possesses five of the eleven ApiAT subfamilies: PfApiAT2 (PfApiAT2/MFR4: PF3D7_0914700), PfApiAT4 (MFR5: PF3D7_1129900), PfApiAT8 (NPT1: PF3D7_0104800), PfApiAT9 (MFR2: PF3D7_0104700) and PfApiAT10 (MFR3: PF3D7_0312500). Previous work in the rodent malaria species Plasmodium berghei (Pb) and the related Apicomplexan parasite Toxoplasma gondii (Tg) showed that PbApiAT8 (or PbNPT1) and several other TgApiATs are localized at the PPM [29][30][31][32] and possess amino acid transport activity 25,26,[29][30][31][32][33][34] . To date, only PbApiAT4 has been shown to play an important role in parasite proliferation within erythrocytes 35 .…”
Section: Introductionmentioning
confidence: 99%
“…6B ), i.e., the “Simple 1” motif, which is common to calcium-dependent kinases ( 14 , 15 ). This motif was also found to be enriched among phosphosites that were hypophosphorylated in P. falciparum schizonts upon conditional knockdown of PfCDPK1 ( 16 ) and PfCDPK5 ( 17 ). Importantly, though, the enriched motifs were further modulated by flanking residues to produce recognition motifs specific to each kinase (see Data Set S3 in the supplemental material).…”
Section: Resultsmentioning
confidence: 88%
“…The CDPKs are unique to plants and some protists, including apicomplexans. Blomqvist et al recently identified 50 proteins with significantly reduced phosphorylation using a conditional CDPK5 knockdown ( Blomqvist et al, 2020 ). An enrichment analysis of these 50 proteins based on gene ontology showed significant enrichment for proteins with transport and transmembrane transport activity, as well as proteins located in vesicles and the cell periphery, consistent with artemisinin resistance mechanisms involving endocytosis.…”
Section: Discussionmentioning
confidence: 99%